Electron transport in carbon nanotubes - Yuan, Shaoning (2009)
This thesis presents the main findings in my PhD project on the electron transport properties of carbnno nanotubes (CNTs) and CNT-based field-effect transistors (FETs). The hysteretic transfer characteristics of CNTFETs are firstly discussed with main focus on surfactant effects on the transfer curves. Afterwards, in-situ Raman scattering of an individual double-walled CNT-based CNTFET is conducted and the mechanism of the intershell interaction of the double-walled CNTs (DWNTs) are studied. The correlations between the in-situ Raman scattering and hysteretic transfer characteristics of the DWNT-FET are then presented. Through these correlations, the inferences of the Si3N4 passivation and the effects of bundled DWNTs on the electron transport properties are investigated.